The symptomatology of psychological trauma in the aftermath of war (1945–1980): UK army veterans, civilians and emergency responders. Issue 5 (21st June 2018) - Engelbrecht, Alberta; Burdett, Howard; Silva, Maria João; Bhui, Kamaldeep; Jones, Edgar
Abstract: Background: UK veterans suffering from a psychological or psychiatric illness as a consequence of service in the Second World War were entitled to a war pension. Their case files, which include regular medical assessments, are a valuable resource to investigate the nature, distribution and duration of symptoms. Methods: A standardised form was used to collect data from pension records of a random sample of 500 UK army veterans from the first presentation in the 1940s until 1980. Data were also gathered from 50 civilians and 54 emergency responders with a pension for post-traumatic illness following air-raids. Results: The 10 most common symptoms reported by veterans were anxiety, depression, sleep problems, headache, irritability/anger, tremor/shaking, difficulty completing tasks, poor concentration, repeated fears and avoidance of social contact. Nine of the 10 were widely distributed across the veteran population when symptoms were ranked by the number of subjects who reported them. Nine symptoms persisted significantly longer in the veteran sample than in emergency responders. These included seven of the most common symptoms, together with two others: muscle pain and restlessness. The persistence of these symptoms in the veteran group suggests a post-traumatic illness linked to lengthy overseas service in combat units. Conclusions: The nature and duration of symptoms exhibited by veterans may be associated with their experience of heightened risks. Exposure to severe or prolonged trauma seems to be associated with chronic multi-symptom illness, symptoms of post-traumatic stress and somatic expressions of pain that may delay or complicate the recovery process.